Effects of sport-specific training intensity on sleep patterns and psychomotor performance in adolescent athletes - Suppiah, H. T.; Low, C. Y.; Chia, M. (Pediatric Exercise Science, 2016)
Purpose: Adolescent student-athletes face time constraints due to athletic and scholastic commitments, resulting in habitually shortened nocturnal sleep durations. However, there is a dearth of research on the effects of sleep debt on student-athlete performance. The study aimed to (i) examine the habitual sleep patterns (actigraphy) of high-level student-athletes during a week of training and academic activities, (ii) ascertain the effects of habitual sleep durations experienced by high-level student-athletes on psychomotor performance, and (iii) examine the impact of sport training intensities on the sleep patterns of high-level student-athletes that participate in low and high intensity sports. Methods: Sleep patterns of 29 high-level student-athletes (14.7 ± 1.3 yrs) were monitored over 7 days. A psychomotor vigilance task was administered on weekdays to ascertain the effects of habitual sleep durations. Results: Weekend total sleep time was longer than weekdays along with a delay in bedtime, and waketimes. Psychomotor vigilance reaction times on Monday were faster than on Thursday and Friday, with reaction times on Tuesday also faster than on Friday. False starts and lapses were greater on Friday compared with Monday. Conclusion: There was a negative impact of sleep debt on student-athletes psychomotor performance.